Optimasi DOCR Pada Sistem Distribusi Loop dengan Pembangkit Tersebar Menggunakan Algoritma Modified Particle Swarm Optimastion (MPSO) - Rahmatullah, Daeng; Yan Dewantara, Belly (J-Eltrik, 2019)
To design the coordination of protection on radial systems is not difficult, but the loop system is challenging for researchers, plus loop systems connected with distributed generators (DG). For setting up Directional Overcurent Relay (DOCR) in loop system only use lowset, so the operating time of release depends on rated of fault current. The fault current will vary if there is DG in the system. Change ON/ OFF DG will also make the direction of the current fluctuate. So we have to reset the protection relay. To re-setting the protection system researchers need more time. The Modified Particle Swarm Optimation (MPSO) method is recommended to reduce the calculation time of the protection relay and obtain the most optimum protection time in loop system with DG. Full load ampere (IFLA) equipment and Maximum fault current (Isc max) as inputs MPSO and lowset as outputs MPSO. Lowset output of MPSO then put on rele as setting DOCR. The results of this study have been tested in simulation using ETAP software successfully and it is clear that MPSO method is the right method to obtain the release settings with the most optimum time.